Influence of surface dimensional effects and interband transitions on absorption of light in aluminium - Mеlnichenko, L.Yu.; Tytarchuk, B.B.; Shaykevich, I.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Optical conductivity of aluminium with of large roughness surface were measured by a spectroellipsometric method in visible, near infrared and near ultra-violet region of the spectrum. Aluminium foil was used as a sample. Comparison of the received results for rough and smooth surfaces of aluminium were performed. It is revealed that the absorption peak on the spectral curve of optical conductivity with a maximum near λ = 0.8 mm for a rough surface of aluminium is considerably wider than for smooth surface, although it has less intensity. An additional maxima near λ = 0.35 mm and λ= 0.97 mm take place for rough surface spectrum. The broadening and additional maxima are accounted for the basis of consideration of model of a surface layer of rough surface of aluminium, as heterogeneous thin layer, in which plasma resonance, resonance of optical conductivity, and also the interaction of these resonances with interband transitions occur.